In situ synchrotron X-ray diffraction study of the effect of microstructure and boundary layer conditions on CO2 corrosion of pipeline steels. (January 2015) - Ko, M.; Ingham, B.; Laycock, N.; Williams, D.E.
Highlights: We studied the effects of steel microstructures and local conditions on CO2 corrosion. Microstructure influences the development of surface roughness during corrosion. The effects of Cr alloying, on average, dominate over the effects of microstructure. Spatial segregation of Cr between the phases in the steel may result in localised corrosion. Abstract: This study demonstrates that the nucleation of crystalline scales of siderite and chukanovite onto the surface of low-alloy steels under CO2 corrosion at elevated temperature is critically dependent on initial surface roughness, on microstructure-related surface roughness developed during corrosion, and on stirring in the solution. This study confirms that effects due to chromium micro-alloying in the steel are extremely important for siderite nucleation. On average, these effects dominate over the effects of microstructure. However, spatial variation of the corrosion deposit thickness indicates an interdependence between microstructure and chromium-enhanced siderite nucleation with the possibility of localised corrosion developing as a result.